Leukocyte engagement of fibrin(ogen) via the integrin receptor α(M)β(2)/Mac-1 is critical for host inflammatory response in vivo - Flick, Matthew J. (American Society for Clinical Investigation, 2004)
The leukocyte integrin α(M)β(2)/Mac-1 appears to support the inflammatory response through multiple ligands, but local engagement of fibrin(ogen) may be particularly important for leukocyte function. To define the biological significance of fibrin(ogen)-α(M)β(2) interaction in vivo, gene-targeted mice were generated in which the α(M)β(2)-binding motif within the fibrinogen γ chain (N(390)RLSIGE(396)) was converted to a series of alanine residues. Mice carrying the Fibγ(390–396A) allele maintained normal levels of fibrinogen, retained normal clotting function, supported platelet aggregation, and never developed spontaneous hemorrhagic events. However, the mutant fibrinogen failed to support α(M)β(2)-mediated adhesion of primary neutrophils, macrophages, and α(M)β(2)-expressing cell lines. The elimination of the α(M)β(2)-binding motif on fibrin(ogen) severely compromised the inflammatory response in vivo as evidenced by a dramatic impediment in leukocyte clearance of Staphylococcus aureus inoculated into the peritoneal cavity. This defect in bacterial clearance was due not to diminished leukocyte trafficking but rather to a failure to fully implement antimicrobial functions. These studies definitively demonstrate that fibrin(ogen) is a physiologically relevant ligand for α(M)β(2), integrin engagement of fibrin(ogen) is critical to leukocyte function and innate immunity in vivo, and the biological importance of fibrinogen in regulating the inflammatory response can be appreciated outside of any alteration in clotting function.